Diseño de un modelo de control interno para la operación del departamento de cobranzas de la central de riesgo Innovation Group S.A. - Badillo Tobar., Andrea Estefany (2013)
The “Innovation Group S.A.” company begins a process of organizational strengthening and development whose guidelines must be enrooted through a process of Inner Control Design into the operations of billing department, to guide efforts of the employees in the medium and long therm. Prior to the Inner Control Design itself, it was detected that the company does not count with the appropriate control system which is why there are several drawbacks in the billing department.